A Companion to African Cinema, Kenneth Harrow and Carmela Garritano (eds) (2019). (1st March 2020) - Mututa, Addamms Songe
A Companion to African Cinema, Kenneth Harrow and Carmela Garritano (eds) (2019)Hoboken, NJ: John Wiley & Sons, 515 pp., ISBN 978-1-11910-005-8, ePDF $172.99, ISBN: 978-1-119-10031-7, h/bk $215